Urinary Dopamine Levels Can Predict the Avidity of Post-Therapy [131I]MIBG Scintigraphy in Unresectable or Metastatic Pheochromocytomas and Paragangliomas: A Preliminary Clinical Study - Junki Takenaka; Shiro Watanabe; Takashige Abe; Satoshi Takeuchi; Kenji Hirata; Rina Kimura; Hiroshi Ishii; Naoto Wakabayashi; Mungunkhuyag Majigsuren; Kohsuke Kudo (Pharmaceuticals)
Background/Objectives: Pheochromocytomas and paragangliomas (PPGLs) are rare neuroendocrine tumors that produce catecholamines. Unresectable or metastatic PPGLs are treated with [131I]metaiodobenzylguanidine (MIBG), but MIBG avidity is often heterogeneous. Identifying predictive factors for non-avid lesions on scintigraphy is clinically important. The primary objective of this study was to investigate the relationship between MIBG avidity and catecholamine secretion patterns in patients with unresectable or metastatic PPGLs. Methods: This retrospective study included 27 patients treated with [131I]MIBG for unresectable/metastatic PPGLs between 2001 and 2024. Patients received a single intravenous dose of [131I]MIBG (5.5–7.4 GBq), with post-therapy scintigraphy performed 3–7 days later. Non-avid lesions were assessed by imaging and confirmed using CT, MRI, and FDG-PET. Clinical factors, including age, sex, prior treatments, metastasis sites, and urine catecholamines, were evaluated using univariate logistic analysis. Predictive factors were assessed via receiver operating characteristic curves. Results: Non-avid lesions were found in nine patients (33.3%). These patients were younger (median age 38 vs. 62.5 years) and had higher urine dopamine levels (median 1510 vs. 779 μg/day) than those without non-avid lesions. Younger age (odds ratio: 0.892, p < 0.01) and higher urinary dopamine levels (odds ratio: 1.003, p < 0.01) were significantly associated with non-avid lesions. All patients > 45 years with urinary dopamine < 1190 μg/day had no non-avid lesions, whereas patients < 45 years with urinary dopamine > 1190 μg/day had non-avid lesions. Conclusions: Age and urinary dopamine levels may predict non-avid lesions in unresectable/metastatic PPGLs, aiding treatment decisions for [131I]MIBG therapy. This article is a revised and expanded version of a paper entitled “Urine dopamine level and age can predict non-avid lesion on scintigraphy after I-131 MIBG treatment for unresectable/metastatic PPGL”, which was presented at SNMMI 2024, Toronto, from 8 June to 11 June 2024.